356 Intranasal administration of novel bacterial therapeutics reduces colonization of the bovine respiratory pathogen Mannheimia haemolytica in challenged calves. (7th December 2018) - Amat, S; Timsit, E; Alexander, T
Abstract: Prevention of bovine respiratory disease (BRD) in cattle entering feedlots is primarily achieved through metaphylactic antibiotic administration. However, the emergence of resistant bacteria poses a threat to veterinary medicine, and necessitates the development of antibiotic-alternatives. We previously isolated and characterized Lactobacillus strains from the nasopharynx of feedlot cattle, for development as bacterial therapeutics (BT) to mitigate the BRD pathogen Mannheimia haemolytica . In the present study, we further characterized these strains by testing their in vivo effectiveness in reducing colonization by M. haemolytica, stimulating an immune response, and altering the nasopharyngeal microbiota in challenged calves. For this, Holstein calves (N=24; 1–3 wks old) were randomly assigned into one of two groups (n=12): BT calves received an intranasal cocktail of four Lactobacillus species in equal concentrations (3 × 10 9 CFU) on d1; and control calves received saline. After 24h of BT inoculation, all calves were challenged intranasally with M. haemolytica (3 × 10 8 CFU). Samples of nasopharyngeal swabs and blood (d0, 3, 5, 7, 9, 11 and 14) were collected. Swabs were plated to enumerate M. haemolytica and lactic-acid bacteria (LAB). In addition, DNA was extracted and the 16S rRNA was sequenced from swabs. Blood samples were evaluated by ELISA for cytokines (IL-6, IL-8 and IL-10). Administration of BT decreased the number of M. haemolytica colonizing calves, as determined by plating ( P = 0.024), while high-throughput sequencing showed a numeric decrease in genus Mannheimia ( P >0.05). No difference in LAB counts by plating or sequencing was found, and serum concentrations of cytokines were not different between the two groups ( P >0.05). Overall, the administration of Lactobacillus reduced colonization by M. haemolytica in calves. This study showed the potential for developing BT to mitigate BRD bacterial pathogens.